Florida Panhandle Healthy Start A Randomized Trial of Prenatal Home Visitation / Isabel Stabile and Mimi Graham. - Stabile, Isabel (Distributed by ERIC Clearinghouse, 2000)
Noting prenatal and early childhood home visitation by nurses has had positive effects on birth outcomes in several at-risk populations, this study examined the impact of weekly home visits by systematically trained visitors on birth outcomes of high-risk pregnant women within the context of a Florida Healthy Start project. Participating were eligible pregnant women in 6 Florida counties; 359 were randomly assigned to the treatment group and 169 to the control group. In addition to prenatal care, treatment group women received weekly home visits by nurses or paraprofessional home visitors who promoted healthy lifestyles, coordinated services, and provided education/support through a community network. Control-group women received services available in the community. Results indicated no statistically significant differences in low birth weight, preterm birth, or poor birth outcome between the treatment and control groups. Women with poor previous birth outcomes were 2.9 times more likely to have a poor birth outcome than women without such experience. Women who received services (independent of group status) had lower rates of low birth weight, preterm birth, and poor birth outcomes. Samples were identified as at much greater risk of poor pregnancy outcome than a comparison group of the general pregnant population in Florida during the same time period, contributing to the inability to demonstrate a significant treatment effect on birth outcomes. (Contains 15 references.) (KB)